How Does Exposure to Covid-19 Influence Health and Income Inequality Aversion? - Miqdad Asaria; Joan Costa-i-Font; Frank Cowell (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study the determinants of individual aversion to health and income inequality in three European countries and the effects of exposure to COVID-19 including the effect employment, income and health shocks using representative samples of the population in each country. Comparing levels of health- and income-inequality aversion in the UK between the years 2016 and 2020 we find a significant increase in inequality aversion in both income and health domains. Inequality aversion is higher in the income domain than in the health domain and inequality aversion in both income and health domains is increasing in age and education and decreasing in income and risk appetite. However, people directly exposed to major health shocks during the COVID-19 pandemic generally exhibited lower levels of aversion to both income and health inequality. But for those at high risk of COVID-19 mortality who experienced major health shocks during the pandemic, inequality aversion was significantly higher than for those of similar individuals experiencing a health shock prior to the pandemic.
Keywords: I18; I30; I38; 330; inequality aversion; income; health; Covid-19; attitudes to inequality; employment shocks; health shocks; difference in differences